Synthesis and Characterization of Cephalosporin Antibiotics - SHRIVASTAVA, SARITA; MURALIKRISHNA, DANTU (Asian Journal of Chemistry, 2010)
In present studies, the synthesis, characterzation and stability of cephalosporin antibiotics are described.